Pengaruh Supervisory Behavior, Budaya Organisasi dan Motivasi - Mariana Mariana; Aryana Satrya; Wilfridus B.Elu (Ridwan Institute, 2021)
Each organization has a goal that it wants to achieve, namely the survival of the organization. Human resources are one of the most important production factors, without which their organization will have difficulty in achieving the goal. Thisresearch was organized to analyze and find out the factors that influence turnover intention in my school. This study uses sampling techniques where all 119 teachers are used as samples and data obtained from questionnaires are processed using Structural Equation Model (SEM) analysis techniques using Partial Least Square (PLS). The results of the analysis show that all hypotheses are accepted. There is a positive and significant influence of supervisory behavior, organizational culture and motivation on job satisfaction. There is a negative and significant influence of supervision behavior, organizational culture, motivation and job satisfaction on turnover intention. In the results of the indirect influence test found supervision behavior, organizational culture and motivation have an influence on turnover intention through mediation of job satisfaction. With demikian the tenth hypothesis is accepted. The results of this study show that in order to reduce turnover rates, management should pay attention to the job satisfaction of teachers in schools or employees at companies and thevariables that affectthem.